Analysis Of The Incidence Asphyxia Neonatorum At Ansari Saleh General Hospital Banjarmasin - Desilestia Dwi Salmarini; Sismeri Dona; Fhera Nanda Azhari (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: According to Research and Development Center Health Ecology in 2001, the pattern of maternal deaths in early neonatal infants (newborns - 7 days) is more due to birth asphyxia, 48 per 1,000 live births (33.6%). Based on preliminary study results conducted on December 23, 2016, data that have been obtained by researchers about the number of asphyxia cases at Ansari Saleh General Hospital Banjarmasin in 2016 that is as many as 941 babies and who died as many as 25 caused by asphyxia.Objective: To analyze factors related to the incidence of asphyxia in Ansari Saleh General Hospital Banjarmasin period November 2016 until March 2017.Method: Descriptive Analytical Research with a Cross-Sectional approach. Sampling is 1,251. A sample of 923 infants, taken by Simple Random Sampling technique. Data were analyzed using chi-square testResults: The results of this study showed that there was a correlation between maternal age and asphyxia cases p-value = 0,000, there was a relationship between mother parity with asphyxia p-value = 0,008, no mother preeclampsia relationship with asphyxia p-value = 0,911, there was relationship between maternal anemia incidence of asphyxia p-value = 0,007, there is correlation between per abdominal labor incidence of p-value = 0,002, there is relationship of birth weight with incidence of asphyxia p-value = 0,001Conclusion: There was a significant relationship between age, parity, per abdominal delivery and birth weight and no association between maternal preeclampsia and asphyxia.Â Keywords: Infant Mortality Rate, Newborn Infant, Early Neonatal Infant, Asphyxia Neonatorum